Terrace formation and preservation: Santa Catalina Island and other California Channel Islands. (4th March 2022) - McInnis, Margarita; Pinter, Nicholas
ABSTRACT: Uplifted coastal terraces are present on Santa Catalina Island, but so poorly preserved that researchers have debated for more than a century whether they even exist. Morphometric analyses of LIDAR-based topography on the California Channel Islands suggest that the poor expression of terraces on Catalina Island is due a combination of (1) geological conditions less conducive to terrace formation than on the other Channel Islands and (2) high landslide susceptibility around Catalina's coastal margin that is erasing terrace morphology and deposits before they can reach the island's relatively un-dissected interior. Both of these factors seem to be related to the mechanical properties of the island's predominant rock type, the Catalina Schist. Several of the other Channel Islands – such as Santa Barbara, San Clemente, Anacapa, and San Miguel Islands – have topography that is dominated by their terrace morphology, mostly by virtue of the small size of those islands. Of the large islands, Santa Rosa has the most extensive terraces, apparently driven by the prevalence of shallowly dipping sedimentary rock. Looking at terrace preservation generally, subhorizontal sedimentary units seem to represent an optimum between promoting the initial creation of wide terrace platforms and resistance to terrace erosion thereafter.